Oxidative Indole Dearomatization for Asymmetric Furoindoline Synthesis by a Flavin‐Dependent Monooxygenase Involved in the Biosynthesis of Bicyclic Thiopeptide Thiostrepton. Issue 15 (3rd March 2021) - Lin, Zhi; Xue, Yufeng; Liang, Xiao‐Wei; Wang, Jian; Lin, Shuangjun; Tao, Jiang; You, Shu‐Li; Liu, Wen
Abstract: The interest in indole dearomatization, which serves as a useful tool in the total synthesis of related alkaloid natural products, has recently been renewed with the intention of developing new methods efficient in both yield and stereoselective control. Here, we report an enzymatic approach for the oxidative dearomatization of indoles in the asymmetric synthesis of a variety of furoindolines with a vicinal quaternary carbon stereogenic center. This approach depends on the activity of a flavin‐dependent monooxygenase, TsrE, which is involved in the biosynthesis of bicyclic thiopeptide antibiotic thiostrepton. TsrE catalyzes 2, 3‐epoxidation and subsequent epoxide opening in a highly enantioselective manner during the conversion of 2‐methyl‐indole‐3‐acetic acid or 2‐methyl‐tryptophol to furoindoline, with up to >99 % conversion and >99 % ee under mild reaction conditions. Complementing current chemical methods for oxidative indole dearomatization, the TsrE activity‐based approach enriches the toolbox in the asymmetric synthesis of products possessing a furoindoline skeleton. Abstract : An enzymatic approach for oxidative indole dearomatization is reported. TsrE, a flavin‐dependent monooxygenase involved in the biosynthesis of bicyclic thiopeptide antibiotic thiostrepton, catalyzes 2, 3‐epoxidation and subsequent epoxide opening during the conversion of 2‐methyl‐indole‐3‐acetic acid or 2‐methyl‐tryptophol to furoindoline, with up to >99 % conversion and >99 % ee under mild reaction conditions.